Layered P2-NaxMn3/4Ni1/4O2 Cathode Materials For Sodium-Ion Batteries: Synthesis, Electrochemistry and Influence of Ambient Storage - Pfeiffer, Lukas Fridolin; Jobst, Nicola; Gauckler, Cornelius; Lindén, Mika; Marinaro, Mario; Passerini, Stefano; Wohlfahrt-Mehrens, Margret; Axmann, Peter (Frontiers in Energy Research, 2022)
Sodium-ion batteries promise efficient, affordable and sustainable electrical energy storage that avoids critical raw materials such as lithium, cobalt and copper. In this work, a manganese-based, cobalt-free, layered NaxMn3/4Ni1/4O2 cathode active material for sodium-ion batteries is developed. A synthesis phase diagram was developed by varying the sodium content x and the calcination temperature. The calcination process towards a phase pure P2-Na2/3Mn3/4Ni1/4O2 material was investigated in detail using in-situ XRD and TGA-DSC-MS. The resulting material was characterized with ICP-OES, XRD and SEM. A stacking fault model to account for anisotropic broadening of (10l) reflexes in XRD is presented and discussed with respect to the synthesis process. In electrochemical half-cells, P2-Na2/3Mn3/4Ni1/4O2 delivers an attractive initial specific discharge capacity beyond 200 mAh g−1, when cycled between 4.3 and 1.5 V. The structural transformation during cycling was studied using operando XRD to gain deeper insights into the reaction mechanism. The influence of storage under humid conditions on the crystal structure, particle surface and electrochemistry was investigated using model experiments. Due to the broad scope of this work, raw material questions, fundamental investigations and industrially relevant production processes are addressed.